Employee Engagement as Mediator Distributive Justice, Islamic Workplace Spirituality, and Work Life Balance on Employee Performance in Islamic Banking - Wahyuningsih, Nining; Aziz, Abdul; Rosnidah, Ida; Layaman, Layaman (Ekonomi Syariah IAIN Kudus, 2026)
This study aims to examine the influence of distributive justice, Islamic spirituality in the workplace, and work-life balance on employee performance through employee engagement. This study develops the variables of workplace spirituality and work-life balance from an Islamic perspective. This study uses a quantitative approach with a saturated sampling technique. Data were collected through a questionnaire from 323 Sharia Bank employees in Cirebon City and Regency, Indramayu Regency, Majalengka Regency, and Kuningan Regency. Data analysis used SEM PLS processed using smart-PLS software. The results of the study indicate that in the direct influence test, namely distributive justice, Islamic spirituality in the workplace and work-life balance have a significant positive effect on employee performance. Likewise, indirect influences, namely distributive justice, have a significant effect on employee performance through employee engagement, and Islamic spirituality in the workplace has an effect on employee performance through employee engagement, and work-life balance has a positive effect on employee performance through employee engagement. The findings of this study confirm organizational behavior theory and reinforce social exchange theory, which holds that high engagement fosters enthusiasm and dedication to work, thereby improving performance. Likewise, Islamic spiritual values need to be implemented beyond mere symbolic meaning.